"Fatal Gastrointestinal and Peritoneal Ischemic Disease" of Unknown Cause at Arba Minch Hospital, Southern Ethiopia. (23rd October 2018) - Feyisa, Jilcha Diribi; Kenea, Melka; Gashaw, Efrem; Getahun, Eskezyiaw Agedew; Hicks, Barry Leon; Desalegn, Hailemichael
Abstract : Gastrointestinal and peritoneal ischemic disease due to unknown etiology present with intestinal obstruction and/or peritonitis otherwise in healthy patient emerged as fatal disease at Arba Minch General Hospital. This disorder was diagnosed based on intraoperative finding. Clinical presentation and natural history of disease progression were similar. It is estimated that about 6–10 lives are being claimed each year at Arba Minch Hospital with this disease of unidentified cause accounting for the largest figure of surgical department. Here we report case analysis and literature review illustrating clinical presentation, workup, preoperative diagnosis, intraoperative diagnosis, and final outcome of fatal gastrointestinal and peritoneal ischemic disease.